Determinação cromatográfica e eletroforética de diuréticos e laxantes em formulações farmacêuticas a base de plantas medicinais - Moreira, Ana Paula Lançanova (2012)
The use of herbal medicines as an alternative treatment has increased by the belief that natural products do not cause damage to health. However cases in which natural products are added of synthetic drugs not declared, presumably to enhance the effectiveness them have been reported in the literature. In the case of weight loss formulations the main adulterants found are appetite suppressants, antidepressants, benzodiazepines, diuretics and laxatives. The identification of these frauds is only possible by applying the analytical methods able to detect the presence of adulterants in the formulations. This paper describes the development of two methods employing separation techniques with electrochemical detection for the determination of diuretics and laxatives as adulterants in herbal products. The method employing capillary zone electrophoresis (CZE) with contactless conductivity detection (C4D) allows the simultaneous determination of amiloride, chlorthalidone, hydrochlorothiazide, furosemide and phenolphthalein in the following optimized conditions: working electrolyte phosphate buffer 20 mmol L-1 (pH 9.2) containing 30% methanol (v/v) separation potential -15 kV, temperature 25 °C, injection hydrodynamic by gravity in 20 cm for 60 seconds. The method employing ion pair chromatography (IPC) with pulsed amperometric detection (PAD) allows the determination of hydrochlorothiazide, chlorthalidone and furosemide on the following conditions: mobile phase phosphate buffer 5 mmol L-1 (pH 4.5) containing SDS 0.3 mmol L-1 and 50% methanol (v/v), sample potential of +0.8 V, the cleaning potential of -0.2 V and +1.0 V, and flow rate of 1.0 mL/min. Both methods were validated in the parameters of linearity, limit of detection limit of quantification, precision, accuracy and selectivity, and were applied in the analysis of 26 samples of natural weight loss products purchased from pharmacies in nine Brazilian states. In three of 26 samples were identified the presence of illegal diuretic hydrochlorothiazide in concentrations ranging from 0.6 to 7.0 mg/capsule. In addition, five other samples called naturals contained declared on the label of the packaging the presence of synthetic diuretics hydrochlorothiazide or furosemide. Both methods were able to identify the adulterants present in samples with high selectivity and sensitivity. Furthermore, they presented very approximate results in the concentration of adulterants found in the formulations. There is still no unified regulation established by the government for control of herbal products. Each country has its laws, but the marketing is global. Maybe this is the reason why the adulteration of natural products has been a recurring practice in various parts of the world. Therefore, effective regulation for the natural products can result in the reduction of these offenses, and punishment of offenders, thus ensuring the rights of consumers to make quality treatment, safe and effective, without prejudice to health. Keywords: Pharmaceutical formulations, adulterants, diuretics, laxatives, methods of separation, electrochemical detection.